Cell-Dependent Pathogenic Roles of Filamin B in Different Skeletal Malformations. (4th July 2022) - Wu, Huixiao; Wang, Yanzhou; Chen, Xinyu; Yao, Yangyang; Zhao, Wanyi; Fang, Li; Sun, Xiaoqing; Wang, Ning; Jiang, Jie; Gao, Ling; Zhao, Jiajun; Xu, Chao
Abstract : Mutations of filamin B ( FLNB ) gene can lead to a spectrum of autosomal skeletal malformations including spondylocarpotarsal syndrome (SCT), Larsen syndrome (LRS), type I atelosteogenesis (AO1), type III atelosteogenesis (AO3), and boomerang dysplasia (BD). Among them, LRS is milder while BD causes a more severe phenotype. However, the molecular mechanism underlying the differences in clinical phenotypes of different FLNB variants has not been fully determined. Here, we presented two patients suffering from autosomal dominant LRS and autosomal recessive vitamin D-dependent rickets type IA (VDDR-IA). Whole-exome sequencing revealed two novel missense variants in FLNB, c.4846A>G (p.T1616A) and c.7022T>G (p.I2341R), which are located in repeat 15 and 22 of filamin B, respectively. The expression of FLNB I2341R in the muscle tissue from our LRS patient was remarkably increased. And in vitro studies showed that both variants led to a lack of filopodia and accumulation of the mutants in the perinuclear region in HEK293 cells. We also found that c.4846A>G (p.T1616A) and c.7022T>G (p.I2341R) regulated endochondral osteogenesis in different ways. c.4846A>G (p.T1616A) activated AKT pathways through inhibiting SHIP2, suppressed the Smad3 pathway, and impaired the expression of Runx2 in both Saos-2 and ATDC5 cells. c.7022T>G (p.I2341R) activated both AKT and Smad3 pathways and increased the expression of Runx2 in Saos-2 cells, while in ATDC5 cells it activated AKT pathways through inhibiting SHIP2, suppressed the Smad3 pathway, and reduced the expression of Runx2. Our study demonstrated the pathogenic mechanisms of two novel FLNB variants in two different clinical settings and proved that FLNB variants could not only directly cause skeletal malformations but also worsen skeletal symptoms in the setting of other skeletal diseases. Besides, FLNB variants differentially affect skeletal development which contributes to clinical heterogeneity of FLNB-related disorders.